Pengaruh Bauran Pemasaran dan Faktor Personal Terhadap Kepuasan Pelanggan Dengan Keputusan Pembelian sebagai Intervening - Soelama, Pricilia Christy (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The results of this study can be seen that the marketing mix variables significantly influence purchasing decisions. And partially the marketing mix also has a significant effect on customer satisfaction. Personal factors have a significant effect on purchasing decisions. Partially personal factors have a significant effect on Customer Satisfaction. Whereas, Purchasing Decisions have a significant effect on Customer SatisfactionKeywords: Marketing Mix, Personal Factor, Purchasing Decision, Customer Satisfaction